Lithological Differences in the Deposits of Closed Basins in the Upper Parsęta Catchment (Western Pomerania) - Major, Maciej (Quaestiones Geographicae, 2011)
Basins without outlets, found in abundance in West Pomerania, display a great lithological diversity. Differences in the lithology in the upper Parsęta catchment result from the processes of areal deglaciation during the Vistulian Glaciation (Karczewski 1989). Intraglacial accumulation, action by fluvioglacial water, and direct glacial accumulation have produced various sedimentary series and their mosaic-like pattern. The youngest sedimentary series have developed during fluvial, aeolian and organogenic accumulation (Kostrzewski et al. 1994a). The lithology of most of the closed basins in the catchment largely features fine diamictic sands which pass into sandy diamicton at 100 cm, then medium diamictic sands which turn into fine sands at depths of 50 and 100 cm, and massive diamictic sands which turn again into sandy diamicton at 100 cm. In the catchment of a closed evapotranspiration basin equipped with measuring instruments, the predominant deposit is sands, especially medium-grained ones. Much less abundant are diamictic sands and sandy diamictons, and silts occur only sporadically. Such a lithological diversity is responsible for different rates of the water cycle recorded in the particular parts of the study area.